Sosialisasi Digital Marketing Menuju UMKM Kreatif Desa Karangrejo Kecamatan Gumukmas Kabupaten Jember - Olga Fatmah Rahmawati; Lucky Wahyu Prasetyo; Adam Maulana; Alviano Lanza; Yusita Titi Hapsari (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2024)
Abstract: This collaborative goal of the KKN program is to advance community development through the use of science and technology, as well as enhancing and developing the community's contributing to the local economy through business management and marketing strategies for small and medium-sized businesses in Karangrejo Village, Gumukmas subdistrict, Jember district. One of the Collaborative KKN group 013 work programs is holding MSME socialization activities which is the first step to educate and provide more insight to MSME actors or the wider community. This socialization carried out in order to improve marketing volume of the business it owns. This socialization raised the theme